Superficial mycosis, at the site or distant to the surgical site, appears to predispose patients to bacterial periprosthetic joint infections. Issue 2 (March 2023) - Lin, Feitai; Li, William T; Fuentes-Rivera, Lorena; Parvizi, Javad
Background: It is traditionally believed that presence of fungal infection in the nail or skin of patients is a risk factor for subsequent infection. The literature is devoid of any evidence to confirm or refute this belief. This study examined a possible relationship between the presence of superficial skin or nail mycoses and subsequent periprosthetic joint infection (PJI) in patients undergoing total joint arthroplasty (TJA). Methods: This is a single-centre, retrospective study of patients who underwent primary TJA between 2000 and 2018. 55 patients with superficial mycoses of skin or nail, at the time of arthroplasty were identified and a variable number matching with up to a 1:5 ratio was performed with 182 patients undergoing TJA who had no superficial mycosis. The groups were further divided into knee and hip TJA. The outcome of TJA in the cohorts was compared. Results: Preoperative demographics were similar between the 2 groups. The incidence of PJI in patients undergoing TKA within a year was significantly higher in patients with superficial mycosis at 8.6% (3/35) compared to 0% (0/120) in patients without mycosis. However, all infections were caused by bacterial species and none were fungal. Multiple regression analysis demonstrated that the presence of superficial mycosis had a strong correlation with development of PJI postoperatively in our TKA cohort. Conclusions: Identification of fungal infection (mycosis) of skin and nail in patients awaiting TJA is important. These patients appear to have a higher risk for developing bacterial PJI than those without fungal infections. Further study is needed to determine if treatment of these patients prior to arthroplasty stands to reverse the high risk for PJI that these patients carry.